The effects of canagliflozin on heart failure and cardiovascular death by baseline participant characteristics: Analysis of the CREDENCE trial. Issue 7 (16th April 2021) - Arnott, Clare; Li, Jing‐Wei; Cannon, Christopher P.; de Zeeuw, Dick; Neuen, Brendon L.; Heerspink, Hiddo J. L.; Charytan, David M.; Agarwal, Anubha; Huffman, Mark D.; Figtree, Gemma A.; Bakris, George; Chang, Tara I‐Hsin; et al.
Abstract: Heart failure is prevalent in those with type 2 diabetes and chronic kidney disease, and is associated with significant mortality and morbidity. In the CREDENCE trial, canagliflozin reduced the risk of hospitalization for heart failure (HHF) or cardiovascular (CV) death by 31%. In the current analysis we sought to determine whether the effect of canagliflozin on HHF/CV death differed in subgroups defined by key baseline participant characteristics. Cox regression models were used to estimate hazard ratios and 95% confidence intervals. Canagliflozin was associated with a reduction in the relative risk of HHF/CV death regardless of age, sex, history of heart failure or CV disease, and the use of loop diuretics or glucagon‐like peptide‐1 receptor agonists (all p interaction > .114). The absolute benefit of canagliflozin was greater in those at highest baseline risk, such as those with CV disease (50 fewer events/1000 patients treated over 2.5 years vs. 20 fewer events in those without CV disease) or advanced kidney disease (estimated glomerular filtration rate [eGFR] 30–45 mL/min/1.73m 2 : 61 events prevented/1000 patients treated over 2.5 years vs. 23 events in eGFR 60–90 mL/min/1.73m 2 ). Canagliflozin consistently reduces the proportional risk of HHF/CV death across a broad range of subgroups with greater absolute benefits in those at highest baseline risk.